Interleukin-27 Ameliorates Atherosclerosis in ApoE-/- Mice through Regulatory T Cell Augmentation and Dendritic Cell Tolerance - Wenbin Xu; Ruirui Zhu; Zhengfeng Zhu; Kunwu Yu; Yue Wang; Yan Ding; Jian Yu; Hongxia Tang; Qiutang Zeng; Yucheng Zhong (Mediators of Inflammation)
Atherosclerosis, which is characterized by chronic inflammation in the arterial wall, is driven by immune cells and cytokines. Recent evidence indicated that interleukin (IL)-27 showed pleiotropic properties in immune diseases. However, precise mechanisms of IL-27, especially in atherosclerosis remains unknown. In our research, we examined the influence of the administration of IL-27 and an anti-IL-27p28 antibody (anti-IL-27p28-Ab) on both the initiation and the progression of atherosclerosis. In the groups (both the initiation and the progression) receiving recombinant IL-27 administration, the formation of atherosclerotic plaques was suspended, and the percentage of regulatory T cells (LAP+ or Foxp3+) in the spleen and peripheral blood was increased. Meanwhile, the number of T helper 1 (Th1) and T helper 17 (Th17) cells was decreased. In the peripheral blood plasma, TGF-β and IL-10 expression were increased, while the levels of IFN-γ and IL-17 were reduced. As for lesions, the mRNA expression of Foxp3, TGF-β, and IL-10 was increased, while that of IFN-γ and IL-17 was reduced. In the anti-IL-27p28 antibody groups, we obtained opposite results. We also observed that DCs treated with IL-27 display a tolerogenic phenotype and that IL-27–treated tolerogenic DCs (tDCs) are likely to play a protective role during atherosclerosis. Our study indicates that IL-27 or adoptive transfer of IL-27 loaded tDCs may be a new therapeutic approach in atherosclerosis.